Asymmetric synthesis of (–)-leiocarpin A via (–)-(S)-goniothalamin employing Julia–Kocienski olefination. Issue 2 (17th January 2016) - Meruva, Suresh Babu; Rao K., Raghavendra; Mohammed, Aaseef; Dahanukar, Vilas H.; Kumar, U. K. Syam; Dubey, P. K.
ABSTRACT: A concise and enantioselective syntheses of antileukemic natural products such as (–)-(S)-goniothalamin and (–)-leiocarpin A has been accomplished in excellent yields. By employing reported conditions on suitable substrates via Julia–Kocienski olefination, intramolecular lactonization, and subsequently dehydroxylative olefination, (–)-(S)-goniothalamin was synthesized. Then Sharpless asymmetric dihydroxylation–intramolecular Michael addition on (–)-(S)-goniothalamin provided (–)-leiocarpin A. GRAPHICAL ABSTRACT: